Application of Differentiated Problem Based Learning to Increase Biology Learning Independence at SMAN 1 Poto Tano - Rohyanti, Sari Dewi; Wahyuni, Tri; Suparman, Suparman (Jurnal Ilmiah Mandala Education (JIME), 2024)
The purpose of this research was to explain whether the application of the differentiated Problem Based Learning (PBL) method was able to increase the independence of biology learning in class XI students at SMA Negeri 1 Poto Tano for the 2022/2023 academic year. This research is Classroom Action Research (PTK) which was carried out in 2 cycles. The research subjects were class XI-2 students, totaling 33 students. The data collection technique used is observation which will be carried out during the learning process. The results of this research indicate that the application of the differentiated Problem Based Learning (PBL) method can increase the biology learning independence of class XI 2 students at SMA Negeri 1 Poto Tano for the 2022/2023 academic year. This can be proven by the increase in student independence in learning from cycle 1 by 68.67%, to 85.45% in cycle 2